The Effect Of Guided Discovery Learning Model Based On Performance Assessment On Students' Science Process Skills In Science Subjects At SMPN 11 Bengkulu Selatan - Boysorongan, Bimon; S, Sukarno; K, Khosi'in (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The academic problems that arise are: Is there a significant influence in the use of the Guided discovery learning model based on performance assessment on students' science process skills at SMPN 11 South Bengkulu. This research method is a quantitative method. Quantitative research is research that is based on the philosophy of positivism, used to research certain populations or samples, collecting data using research instruments, quantitative/statistical data analysis, with the aim of testing predetermined hypotheses. The research results are as follows: Based on the results of research conducted at SMP Negeri 11 South Bengkulu, the results of data analysis and discussion can be concluded that the experimental hypothesis is accepted. This means that